NILAI-NILAI ISLAM DI BALIK PRAKTIK HOSPITAL SOCIAL RESPONSIBILITY - Moh Faisol; Nyimas Wardatul Afiqoh (Jurnal Akademi Akuntansi, 2020)
The aim of this research to understand how to practice the hospital social responsibility in Rumah RSU UMM.. Through six employees as informant’s key of RSU UMM, researcher found that RSU UMM practice HSR by: (1) Giving discounts for hospital charges; (2) Doing charity activities; (3) Spiritual building; (4) Forming a donation account; (5) Permitting the patient go home before paid off hospital charges; (6) Giving equal treatment to employees who has physical limitations; and (7) Managing employees infak. The form and the way of HSR practices which is done reflect that RSU UMM as a business entity is not only profit oriented, but it prioritize the humanitarian aspects (social oriented) and religious aspects (spiritual oriented).